Supracrestal Tissue Attachment (Biologic Width) in Clinical Practice: A Narrative Review - César-Augusto Padilla-Avalos; Consuelo Marroquín-Soto; Gianella Sedano Huaman; Paula Ximena Gómez Restrepo; Rocío Alvarez Medina; Claudio Peña-Soto (Odovtos - International Journal of Dental Sciences, 2026)
The supracrestal tissue attachment, historically referred to as the biologic width, represents a dentogingival unit fundamental for periodontal health and restorative predictability. This narrative review evaluates both conventional and technology-assisted strategies for its preservation. Searches were conducted in PubMed/MEDLINE, Scopus, and Web of Science. Eligible studies encompassed systematic and narrative reviews, consensus statements, clinical trials, comparative studies, and case series. The evidence was critically appraised using the Oxford Centre for Evidence-Based Medicine (OCEBM) framework and synthesized thematically into comparative and recommendation tables. Conventional techniques (gingivectomy, access flaps, osteotomy, and osteoplasty) remain reliable when guided by biologic and prosthetic principles. Laser-assisted procedures enhance soft tissue management through improved precision, effective hemostasis, and reduced morbidity. Digitally guided workflows that integrate CBCT, intraoral scanning, and CAD/CAM technology enable precise mapping and reproducibility, particularly in esthetically demanding cases. Optimal management requires individualized planning that integrates conventional, laser-assisted, and digital approaches within an evidence-based framework, ensuring periodontal stability, restorative longevity, and harmonious esthetic outcomes in clinical practice.